About Jahaz-bhais and Jahazbahens: The Politics of a Transnational Family in Amitav Ghosh’s Sea of Poppies - Bhattacharya, Sajalkumar (EAST WEST JOURNAL OF HUMANITIES, 2011)
Primarily concerned with the South Asian diaspora in the different regions of the world, Amitav Ghosh has set himself the task of narrating an anti-Hegelian history of the world, incorporating hitherto left-out narratives of ordinary people and their attempts to resist the hegemony of the nation through their own stories and search for identity. Interestingly, it is because of this preoccupation with individuals and his postcolonial instinct to foreground their stories that the family has assumed such a central position in all of Ghosh’s narratives. For Ghosh, family stories are always important because it is through them that history is experienced. The familial space in Ghosh, however, is not a passive site. Rather, it offers the individual a space that situates his identity away from the confines of the ’restrictively imagined collectivity’ of the nation. It is an imagined space where bonds of personal love replace the troubled terrain of the nation with all its discontents. At the same time, this familial space is in no way unproblematic since it too involves power. It is a space to create, expand and protect subjectivities. But most importantly, in the fictional world of Ghosh, it is this nature of home that enables it to be relocated transnationally, beyond the ’shadow lines’ of the borders of the home country, in different foreign physical spaces. Ghosh’s basic point seems to be that home is everywhere; it only needs to be reinvented. Ghosh’s characters are able to combat the diasporic angst through their successful engagement in an irresistible quest for the family in transnational locations. My paper aims to explore Ghosh’s latest novel Sea of Poppies from this perspective.